Genetic and codon usage analyses reveal the evolution of the seoul virus - Wei, Yamei; Cai, Yanan; Han, Xu; Han, Zhanying; Zhang, Yanbo; Xu, Yonggang; Jiang, Caixiao; Li, Qi (Frontiers in Genetics, 2025)
IntroductionSeoul virus (Orthohantavirus seoulense, SEOV), a member of the Hantaviridae, causes hemorrhagic fever with renal syndrome (HFRS) through rodent hosts. However, its molecular evolutionary dynamics and codon usage patterns remain poorly understood.MethodsThis study integrated coding sequences from GenBank and previously acquired SEOV strains to systematically analyze genetic evolution and codon usage bias.ResultsIt revealed that SEOV evolved seven clades (A-G) with distinct amino acid variation sites and geographic clustering. Recombination events were identified during evolution, alongside purifying and positive selection on specific sites (e.g., codon 259 in the S segment and codon 11 in the M segment). The three viral segments (L, M, and S) exhibited weak codon usage bias, predominantly driven by natural selection, with host adaptation significantly influencing evolutionary trajectories. The S segment demonstrated the strongest pathogenicity due to its closer codon usage alignment with Homo sapiens (H. sapiens) and Rattus norvegicus (R. norvegicus), whereas the L segment showed the lowest host adaptation. Divergent codon preferences among clades highlighted adaptive strategies in host-virus interactions.ConclusionThese findings elucidate the evolutionary mechanisms of SEOV and provide a theoretical foundation for live attenuated vaccine design and region-specific viral control strategies.